Tiragolumab and TIGIT: pioneering the next era of cancer immunotherapy - Ghasemi, Kosar (Frontiers in Pharmacology, 2025)
Tiragolumab, a monoclonal antibody (mAb) targeting T cell immunoreceptor with Ig and ITIM domains (TIGIT), represents a novel approach in cancer immunotherapy. TIGIT, an immunological checkpoint receptor, suppresses T cell activation and promotes immune evasion in various cancers. By inhibiting TIGIT, Tiragolumab enhances T cell-mediated anti-tumor immunity, particularly when combined with programmed cell death-1 (PD-1) and programmed death-ligand 1 (PD-L1) inhibitors. This synergy arises from complementary mechanisms, where TIGIT blockade reduces CD155-mediated suppression, amplifying PD-1/PD-L1-driven T cell activation. Phase II and III trials, including the CITYSCAPE trial for non-small cell lung cancer (NSCLC), have shown improved objective response rates (37% vs. 21% with PD-L1 inhibitor monotherapy) and progression-free survival (PFS), with manageable adverse effects. However, the potential of other checkpoint inhibitors, such as Lymphocyte Activation Gene 3 (LAG3), T-cell immunoglobulin and mucin domain-3 (TIM-3), or cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), remains underexplored compared to TIGIT. This review summarizes TIGIT’s molecular mechanisms, preclinical and clinical data, and limitations, including resistance mechanisms (e.g., upregulation of alternative checkpoints), biomarker development, and the need for broader investigation into alternative inhibitors to optimize combination therapies for personalized, durable cancer treatment.